The effect of magnocellular-based visual-motor intervention on Chinese children with developmental dyslexia - Qian, Yi; Bi, Hong-Yan (Frontiers in Psychology, 2015)
Magnocellular(M) deficit theory points out that the core deficit of developmental dyslexia (DD) is the impairment in M pathway, which has been evidenced in many previous studies. Based on the M deficit, some researchers found that visual intervention focusing on M deficit improved dyslexics’ M function as well as reading abilities. However, the number and reliability of these training studies were limited. Therefore, the present study conducted an M-based visual-motor intervention on Chinese children with DD to investigate the relationship between M deficit and Chinese DD. Intervention programs included coherent motion detection, visual search, visual tracking and juggling, which were related to M function. The results showed that M function and phonological awareness of training dyslexic group were improved to a normal level as age-matched normal children after intervention, while non-training dyslexics did not. It supported M deficit theory, and suggested M deficit might be the core deficit of Chinese DD.